2016 IEEE 55th Conference on Decision and Control (CDC) 2016
DOI: 10.1109/cdc.2016.7798978
|View full text |Cite
|
Sign up to set email alerts
|

Learning quadrotor dynamics using neural network for flight control

Abstract: Abstract-Traditional learning approaches proposed for controlling quadrotors or helicopters have focused on improving performance for specific trajectories by iteratively improving upon a nominal controller, for example learning from demonstrations, iterative learning, and reinforcement learning. In these schemes, however, it is not clear how the information gathered from the training trajectories can be used to synthesize controllers for more general trajectories. Recently, the efficacy of deep learning in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 18 publications
(39 reference statements)
2
94
0
1
Order By: Relevance
“…It can be shown that this leads to finite-gain L p stability and input-to-state stability (ISS) [29]. Furthermore, the hierarchical combination between s andp in (7) results in lim t→∞ p(t) = lim t→∞ s(t) /λ min (Λ), yielding (14).…”
Section: B Stability Of Learning-based Nonlinear Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that this leads to finite-gain L p stability and input-to-state stability (ISS) [29]. Furthermore, the hierarchical combination between s andp in (7) results in lim t→∞ p(t) = lim t→∞ s(t) /λ min (Λ), yielding (14).…”
Section: B Stability Of Learning-based Nonlinear Controllermentioning
confidence: 99%
“…where the reference angular rate ω r is designed similar to (7), so that when ω → ω r , exponential trajectory tracking of a desired attitude R d (t) is guaranteed within some bounded error in the presence of bounded disturbance torques.…”
Section: A Reference Trajectory Trackingmentioning
confidence: 99%
“…Researchers of system identification for quadrotors also apply machine learning techniques. Bansal et al used NN models of the Crazyflie's dynamics to plan trajectories [5]. Our implementation differs by directly predicting change in attitude with on-board IMU measurements and motor voltages, rather than predicting with global, motion-capture state measurements and thrust targets for the internal PIDs.…”
Section: B Learning For Quadrotorsmentioning
confidence: 99%
“…This paper is the first demonstration of controlling a quadrotor with direct motor assignments sent from a MBRL derived controller learning only via experience. Our work differs from recent progress in MBRL with quadrotors by exclusively using experimental data and focusing on low level control, while related applications of learning with quadrotors employ low-level control generated in simulation [4] or use a dynamics model learned via experience to command on-board controllers [5]. Our MBRL solution, outlined in Figure 1, employs neural networks (NN) to learn a forwards dynamics model coupled with a 'random shooter' MPC, which can be efficiently parallelized on a graphic processing unit (GPU) to execute low-level, real-time control.…”
Section: Introductionmentioning
confidence: 99%
“…This problem has been well studied in literature for both linear systems, e.g. [5], as well as for nonlinear systems using the function approximators such as GP [6]- [8] and neural networks (NN) [9], [10]. However, a model obtained using this open-loop procedure can result in a reduced controller performance on the actual system [4].…”
Section: Introductionmentioning
confidence: 99%